Depression, sleeping pattern, and suicidal ideation among medical students in Bangladesh: A cross-sectional pilot study - Hasan, M. Tasdik; Hossain, Sahadat; Gupta, Rajat Das; Podder, Vivek; Mowri, Naima Afroz; Ghosh, Anindita; Mahmood, Hassan Rushekh; Ahmmed, Faisal; Khatun, M. S. T. Halima; Nodi, Rhedeya Nury; Koly, Kamrun Nahar; Yasmeen, Sharmeen; et al. (Springer Link, 2022)
This article was published in Journal of Public Health: From Theory to Practice by Springer Link [ Copyright © 2020, Springer-Verlag GmbH Germany, part of Springer Nature] and the definite version is available at: https://doi.org/10.1007/s10389-020-01304-0 The Journal's website is at: https://link.springer.com/article/10.1007/s10389-020-01304-0?fbclid=IwAR0j9pbl3BnB3e1R8TdlmlKmR1RXf6FN0m4Npo_xY1v_R1flXQvg0BU5Eq0&Abs1